Clinical characteristics of immunoglobulin G4-positive interstitial pneumonia. Issue 3 (31st August 2021) - Komatsu, Masamichi; Yamamoto, Hiroshi; Matsui, Shoko; Terasaki, Yasuhiro; Hebisawa, Akira; Iwasawa, Tae; Johkoh, Takeshi; Baba, Tomohisa; Miyamoto, Atsushi; Handa, Tomohiro; Tomii, Keisuke; Waseda, Yuko; et al.
Immunoglobulin G4 -related disease is a systemic disease characterised by tumefactive lesions with abundant IgG4 -positive plasma cells and elevated serum IgG4 concentrations [1–4]. We previously assessed IgG4 -related respiratory disease (IgG4 -RRD) with extrathoracic manifestations [5]. IgG4 -RRD develops through the lymphatic routes in the lungs and responds well to corticosteroid therapy with a benign prognosis [5–7]. However, whether interstitial pneumonia (IP) with IgG4 -positive plasma cell infiltration in the lungs without the extrathoracic lesions of IgG4 -related disease could be considered a type of IgG4 -RRD is controversial. This study suggests that IgG4 + IP with abundant IgG4 + cells and elevated serum IgG4 levels could be treated differently from IgG4 -related respiratory disease due to potential differences in disease behaviour and response to corticosteroid therapy https://bit.ly/3dUo2cu